DIAGNOSTICS AND SURGICAL TREATMENT OF DEEP VENOUS THROMBOSIS LOWER LIMBS AND PELVIS - G. G. Khubulava; Е. K. Gavrilov; A. N. Shishkevich; I. A. Larin; Yu. R. Alborov; S. V. Sadovoy (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. Based on our own experience and analysis of the literature, we want to demonstrate the features of diagnosis and treatment of ascending deep phlebothrombosis of the lower limbs and pelvis.MATERIAL AND METHODS. During the period from October 2008 to September 2016, in the First Clinic of Surgery (postgraduate medical education) of ”Military Medical Academy named after S. M. Kirov” we analyzed the results of treatment of 44 patients with this pathology. Selective surgical tactics was based on the evaluating of general status, activity of the patient, the presence of concomitant pathology, complications of the disease. Implantation of the cava-filter was performed in 23 patients. In active patients, without significant concomitant pathology, open thrombectomy operations were performed from the deep veins of the lower limbs or from the inferior vena cava and iliac veins (21 patients). In some of these patients, a removable cava-filter was implanted before thrombectomy (8 patients). Thrombectomy from the deep veins of the lower limbs was supplemented in 12 patients by the plication of the main vein.RESULTS. This tactic made it possible to achieve favorable results in the majority of patients (27 patients, 87 %) – there were no signs of recurrence of venous thromboembolic complications, there was complete or almost complete (more than 90 %) recanalization of thrombosed veins, venous insufficiency was limited by the presence of transient edema. Small hemorrhagic complications were noted in 2 patients. Relapses of venous thromboembolic complications occurred in a distant period in 3 patients. In order to prevent fatal pulmonary embolism, patients with ascending deep phlebothrombosis need surgical treatment.CONCLUSION. The choice of surgical treatment (cava filter implantation, deep vein thrombectomy) should be determined depending on the general status, patient activity, the presence of concomitant pathology, complications of the disease, and also individually in each specific clinical situation.